Tradição e traduções - Previtalli, Ivete Miranda (2012)
This study proposes to reveal the candomblé angola circumscribed in the city of São Paulo, trying to comprehend the moment in which the search for affirmation of it´s identity couples up to the search of it´s African origins. This posture, manifested by some (pais de santo), promotes the dialogue as well as the confrontation among adepts of the Angola nation, pointing to the irreconcilable forces of tradition and translation . In this clash are revealed not only the hybridization process, in which sincretisms are recognised, but also what is no allowed to merge. This way, the oral stories collected from pais and mãe de santo, the observation of parties, the examination of old photographies and informal talks with the adepts, unveiled the questionings,anxieties and resistances that hold at the moment in the São Paulo Angola nation. The search for the imagined Africa can take many paths. But it may not produce africanisms, attest religious orthodoxies or separate nations into fixed frontiers. Besides this, to considerate that angola nation forms a religious continuum with the African Bantu traditional religions will end up dividing nations into pure and mixed , desconsidering constant transformations in ritual practices. In São Paulo, the Afro-Brazilian religious identity, has a cultural origin. The Africa that lives in the angola nation is one marked by diasporization and transformed in the New World. It is this imagined Africa produced by candomble´s narrative that may offer resources for the angola nation today. Even though, as only elements of culture with roots remain and flourish, we can not forget that the original elements were transformed by the process of cultural translation